KORELASI HUKUM INVESTASI DAN KUALITAS INDEKS DEMOKRASI DI INDONESIA - Yusuf Muhamad Said; Sumiryasih (The Juris, 2022)
Indonesia is a developing country that needs foreign investors and local investors in order to increase economic growth and create job opportunities for the increasing number of unemployed. The government believes that effective and efficient regulation will eliminate various obstacles for investors and will reduce the high costs that are often avoided by investors. The formulation of the problem in this study is whether the behavior of investors in general in investing relates to the democratic value of a destination country, and whether a low democracy index and a high corruption index have an impact on capital owners who continue to invest. In this study, the author uses a normative juridical research method, by explaining the analysis of the thing being studied (hermeneutic discipline). With the results of the study that in the study it was found that the growth of the democracy index in Indonesia was stable at low, as well as the corruption index was stable at high, but the investment graph had an upward trend. The decline in investment in a country, especially in Indonesia and Miyanmar, is not due to the improvement in the quality of democracy and low levels of corruption, but is more influenced by the military codeta and the occurrence of riots or riots that are difficult for the security authorities to control.